Interleukin-6 gene polymorphisms correlate with the progression of nephropathy in Chinese patients with type 2 diabetes: A prospective cohort study. (October 2016) - Chang, Wen-Tsan; Huang, Meng-Chuan; Chung, Hsin-Fang; Chiu, Yen-Feng; Chen, Pao-Shan; Chen, Fang-Pei; Lee, Chun-Yi; Shin, Shyi-Jang; Hwang, Shang-Jyh; Huang, Ya-Fang; Hsu, Chih-Cheng
Highlights: Interleukin-6 (IL-6) serves a candidate gene involved in susceptibility to nephropathy. This longitudinal study focused on 568 type 2 diabetes patients with normoalbuminuria. Development of diabetic nephropathy over 5.3 years was examined. IL-6 polymorphisms is associated with progression of nephropathy in diabetic patients. Abstract: Aims: Interleukin-6 (IL-6), an inflammatory cytokine, is considered a candidate gene possibly involved in susceptibility to nephropathy in diabetes. This study aimed to examine whether IL-6 polymorphisms predict the progression of nephropathy in a prospective Chinese cohort of patients with type 2 diabetes. Methods: A total of 568 type 2 diabetic patients with normoalbuminuria at baseline were followed up for a mean of 5.3 ± 1.5 years. Urinary albumin-to-creatinine ratio (ACR) ⩾30 mg/g in two consecutive urine tests were defined as progression to diabetic nephropathy ( n  = 143). Five polymorphisms of IL-6 gene, rs1800795, rs1800796, rs1524107, rs2069837, and rs2069840, were genotyped. Cox proportional hazard models were used to estimate hazard ratio (HR) and 95% CI of progression to diabetic nephropathy under different genetic models. Results: Almost all patients (99.6%) carried the rs1800795 GG homozygous genotypes. In the Cox proportional models adjusted for multiple covariates, the HR under recessive model was 2.02 for rs1800796 GG (vs. CC + CG, 95% CI: 1.08–3.75, p  = 0.027), 2.37 for rs2069837 GG (vs. AA + AG, 95% CI: 1.15–4.87, p  = 0.019), and 2.08 for rs1524107 CC (vs. TT + TC, 95% CI: 1.12–3.89, p  = 0.021). These associations remained significant for rs1800796 and rs1524107 after correction for multiple testing ( α  = 0.017). Overall, our results suggest that rs1800796 GG and rs1524107 CC homozygous genotypes may confer a greater risk for development of nephropathy in type 2 diabetes. Conclusions: IL-6 gene polymorphisms rs1800796 and rs1524107 may serve as predictors of progression of nephropathy in Chinese patients with type 2 diabetes.